Current incidence of certain clostridial infections: gas gangrene and tetanus - E. I. Komarovskaya; O. V. Perelygina (Биопрепараты: Профилактика, диагностика, лечение, 2021)
Clostridial myonecrosis or gas gangrene (myonecrosis) and tetanus are relatively rare nowadays, but they are still considered serious conditions associated with poor prognosis and high mortality. Life-threatening infections caused by Clostridium species have been known and studied for centuries, as they differed from other infections in terms of typical clinical manifestations, challenges of therapy and prevention. The aim of the study was to analyse the global incidence of gas gangrene and tetanus and challenges of prevention and treatment of these diseases. The review of up-to-date scientific literature demonstrated that gas gangrene continues to be a problem due to its rapid progression and challenging treatment. There are two main forms of the disease—traumatic and spontaneous. Traumatic gas gangrene is usually caused by C. perfringens, C. septicum, C. novyi (oedematiens), or C. histolyticum. Its incidence increases dramatically during wars, natural disasters, and other calamities. The literature review demonstrated that over the past 40 years there has been a rise in the frequency of spontaneous gas gangrene caused by C. septicum in people with compromised immune systems, in injecting drug users, and in women during various gynecological procedures and during normal delivery. Despite the effectiveness of the tetanus immunisation programme, the infection remains widespread in countries with insufficient vaccination coverage. The risk of tetanus in developed countries is high among elderly unvaccinated or partially vaccinated people, among injecting drug users, and vaccine refusers. The paper describes some clinical cases of gas gangrene and tetanus which demonstrate problems associated with challenging diagnosis and treatment, low awareness among primary healthcare personnel about mechanisms of anaerobic infection development, and anti-vaccination movement.